Conhecimento de enfermeiros da atenção primária à saúde sobre síndromes hipertensivas específicas da gestação - SIQUEIRA, Lorena Saavedra (Universidade Federal do Pará, 2023)
The Specific Hypertensive Syndrome of Pregnancy (SHEG) is characterized by clinical manifestations such as hypertension and proteinuria, a symptom that manifests itself after the 20th week of pregnancy, is considered the first cause of maternal death in Brazil. In this context, through the inclusion of preventive and curative procedures and health promotion, prenatal care can be considered a protective factor for the health of pregnant women. The nurse is the health professional most qualified to identify, and perform the first care and referral for high-risk pregnant women to prenatal care if necessary. The nursing care practiced by the nurse is permeated by several knowledge and skills that have a strong influence on care during the puerperal pregnancy cycle. It is essential to know and understand pregnancy and its complications for measures to be taken in a timely manner to protect the health of the mother and fetus. Thus, the objective was to unveil the knowledge of nurses who attend prenatal care in basic health units about Specific Hypertensive Syndromes of Pregnancy in the city of Belém, state of Pará. A field research with a qualitative descriptive approach was carried out in the eight administrative districts of Belém, and the sample consisted of fifteen nurses who attend prenatal care in primary care, the collection was made through an oral and recorded interview, the analysis Data analysis was carried out through Bardin's Content Analysis, and to assist in processing, the IRAMUTEQ software was used as a tool that brings statistical rigor to qualitative research carried out according to Reinert's method, which uses the Descending Hierarchical Classification. In the results, four categories and three subcategories emerged. Category 1 “Main aspects about SHEG” with subcategories 1 and 2, respectively, “Knowledge of prenatal nurses about SHEG and its clinical manifestations”, “Preventive measures to reduce complications triggered by SHEG during prenatal care. primary ", category 2" Prenatal care in primary care of pregnant women with SHEG ", with subcategory 1" Factors associated with referral of pregnant women with SHEG to Obstetric Urgencies and Emergencies ", Category 3" Nurses' assistance to pregnant women diagnosed with SHEG "and Category 4" Nurses' knowledge about nutritional factors during pregnancy and the relationship with SHEG ". Nurses who work in prenatal care have knowledge about SHEG, however they have difficulties in its classification, describing the pathology in a more general way. In addition, some clinical signs such as edema are described as a diagnostic criterion, despite the literature demonstrate the opposite. Another relevant factor concerns the prevention of SHEG, where nurses describe healthy habits as protective factors, which according to the evidence only prevent complications that this pathology causes, besides, within the management, a strong tendency to refer to the pre-natural high-risk and obstetric emergencies, however there is no reference to the return of this woman to her unit of origin to share prenatal care as guided by women's health protocols. We concluded that most of the participants had been without training on prenatal care for a long time, which may be related to the outdated information about changes in protocols and inappropriate conduct. Through investigation, we understand the need for professional improvement of nurses on SHEG, and that the creation and use of care protocols based on the most current scientific evidence being addressed in the clinical practice of nurses are extremely important to guide the decision-making process and ensuring the provision of quality and safe care. In this context, we can say that nurses have knowledge about SHEG, however there are still many gaps regarding the proper classification of the pathology, the clinical management within primary care shows a difference in the procedures adopted despite the existence of national protocols.